On-chip ZnO nanofibers prepared by electrospinning method for NO2 gas detection - Nguyen, Van Hoang; Nguyen, Van Dung; Do, Quang Dat; Quan, Thi Minh Nguyet; Chu, Manh Hung; Nguyen, Van Hieu (Communications in Physics, 2018)
In the present study, on-chip ZnO nanofibers were fabricated by means of the electrospinning technique followed by a calcination process at 600 oC towards the gas sensor application. The morphology, composition, and crystalline structure of the as-spun and annealed ZnO nanofibers were investigated by field emission scanning electron microscopy (FESEM), energy dispersive X-ray (EDX), and X-ray diffraction (XRD), respectively. The findings show that spider-net like ZnO nanofibers with a diameter of 60 – 100 nm were successfully synthesized without any incorporation of impurities into the nanofibers. The FESEM images also reveal that each nanofiber is composed of many nanograins. The combination of experimental and calculated X-ray diffraction data indicate that ZnO nanofibers were crystallized in hexagonal wurtzite structure. For the gas sensing device application, the ZnO nanofibers-based sensors were tested with the nitrogen dioxide gas in the temperature range of 200 oC to 350 oC and concentrations from 2.5 ppm to 10 ppm. The sensing property results indicate that at the optimal working temperature of 300 oC, the ZnO nanofibers-based sensors exhibited a maximum response of 30 and 166 times on exposure of 2.5 and 10 ppm NO2 gas, respectively. The presence of nanograins within nanofibers, which results in further intensification of the resistance modulation, is responsible for such high gas response.